Nursing care time in a teaching hospital - Rogenski, Karin Emília; Fugulin, Fernanda Maria Togeiro; Gaidzinski, Raquel Rapone; Rogenski, Noemi Marisa Brunet (Revista da Escola de Enfermagem da USP, 2011)
This is a quantitative exploratory, descriptive study performed with the objective to identify and analyze the performance of the average time of nursing care delivered to patients of the Inpatient Units of the University Hospital at University of São Paulo (UH-USP), from 2001 to2005. The average nursing care time delivered to patients of the referred units was identified by applying of a mathematical equation proposed in the literature, after surveying data from the Medical and Statistical Service and based on the monthly working shifts of the nursing professionals. Data analysis was performed using descriptive statistics. The average nursing care time observed in most units, despite some variations, remained stable during the analyzed period. Based on this observed stability, it is concluded that the nursing staff in the referred HU-USP units has been continuously evaluated with the purposes of maintaining the average time of assistance and, thus, the quality of the care being delivered.